Creating legal worlds : story and style in a culture of argument - Henderson, Greig E. (University of Toronto Press, 2015)
Through careful analyses of notable cases from Canada, the United States, and the United Kingdom, Greig Henderson analyses how the rhetoric of storytelling often carries as much argumentative weight within a judgement as the logic of legal distinctions.